Analisis Tingkat Kebisingan Lalu Lintas pada Kawasan Kampus 1 Universitas Negeri Gorontalo Ditinjau dari Tingkat Baku Mutu Kebisingan yang Diizinkan - C. Mopili; Y. Kadir; M. Mahmud (Civil Engineering Department, Tadulako University, 2023)
An increase in traffic volume causes several negative impacts, one of which is noise. The Campus 1 area of the State University of Gorontalo is one of the education zones where the traffic flow is quite heavy, so a study was conducted to analyze the noise level due to traffic in the area and compare the noise level with the Noise Quality Standard KEP-48/MENLH/11/1996. This research was conducted on roads adjacent to Campus 1 State University of Gorontalo, namely on the roads Jenderal Sudirman (point 1) with road type 2/2 UD, the roads Ir. Hi. Joesoef Dalie (point 2) with road type 4/2 D, and the roads Dewi Sartika (point 3) with road type 2/2 UD. The method used is called